PENILAIAN ASET WARISAN BUDAYA MENGGUNAKAN MARKET APPEALROBUSTICITY MATRIX DI MASJID SRI ALAM DUNIA SIPIROK KABUPATEN TAPANULI SELATAN PROVINSI SUMATERA UTARA - Harahap, Roito; Puspita, Nungky (Journal of Tourism Destination and Attraction, 2024)
Cultural heritage assets are something uniquely valuable from a society or group that is inherited from previous generations and then preserved for future generations. The research design used is mixed methods with quantitative data acting as the main data and qualitative data serving as supporting data in this research. The research results obtained are the preservation of cultural heritage at the Sri Alam Dunia Sipirok Mosque based on the protection aspect, namely by carrying out weekly and routine building maintenance, preventing damage to the main building. In terms of development, it has results by improving community welfare. In the assessment of cultural heritage assets, the results of weighting market appeal and robusticity are included in the high attractiveness category, where the Sri Alam Dunia Sipirok Mosque has high attractiveness and building durability. This has the potential to be used as a recommendation for historical tourist attractions in the area.